Procurement Procedures under the Private Finance Initiative - Craven, Richard (Journal of Malaysian and Comparative Law, 2019)
The EU regulates public procurement in order to open Member States’ markers in public contracts to EU-wide competition. Since the 1970s, it has done this through a series of harmonising directives; these essentially require Member States to implement rules providing for certain public contracts to be awarded in accordance with transparent and non-discriminatory procedures. In 2004 a new procedure was introduced: competitive dialogue. The new procedure is designed specifically with the procurement of complex contracts, such as contracts procured under the UK’s Private Finance Initiative, in mind. Prior to 2004, in the UK these contracts had been procured in a way that the European Commission perceived to lack transparency and competitive tension. The introduction of competitive dialogue seeks to remedy these problems. However, some writers have identified areas of legal uncertainty and areas in which the legal rules may potentially conflict with value for money procurement goals. The paper provides an overview of the new legal rules on competitive dialogue and the regulation of complex procurement in the UK.